Missed case of fever of unknown origin during COVID-19 pandemic: patent ductus arteriosus endarteritis. Issue 5 (27th May 2021) - Batta, Akash; Verma, Samman; Panda, Prashant; Sharma, Yash Paul
Abstract : A 40-year-old woman presented with fever of unknown origin (FUO) for 2 months. Without a definitive diagnosis and having received multiple empirical antibiotics from outside without relief, she was referred to our centre. Cardiac auscultation was remarkable for a grade 3/6 continuous murmur in the upper left sternal border. Echocardiogram revealed a patent ductus arteriosus (PDA) and a 5×7 mm mobile vegetation at the pulmonary artery bifurcation. Blood culture grew Streptococcus mutans. Embolisation of the vegetation to the pulmonary circulation occurred after the start of intravenous antibiotics resulting in fever relapse. Antibiotics were continued for 6 weeks and the fever settled. She underwent device closure of PDA after 12 weeks and is currently doing fine. Infective endocarditis/endarteritis is an important differential in a patient of FUO. A thorough clinical examination is important in every case of FUO, gives an important lead into diagnosis and guides appropriate investigations to confirm it.